Immune modulation of co-transplantation mesenchymal stem cells with islet on T and dendritic cells - Li, F R (Blackwell Science Inc, 2010)
Allogeneic pancreatic islet transplantation theoretically represents a cure for type 1 diabetes. However, current immune suppressive therapies are often associated with undesired side effects. Given this problem, and the shortage of human islet donors, the majority of type 1 diabetes patients cannot currently be offered an islet transplant. However, it has been found that mesenchymal stem cells (MSCs) could exert unique immunosuppressive effects both in vitro and in vivo. Herein we transplanted allogeneic 200 islets alone or in combination with MSCs (3 × 10(6) cells) under the kidney capsules of diabetic C57LB/6 mouse. We found that the ratios of T helper type 1 (Th1) to Th2 and Tc1 to Tc2 were reduced, and the numbers of naive and memory T cells were down-regulated in peripheral blood after transplantation. In addition, the maturation, endocytosis and interleukin-12 secretion of dendritic cell (DCs)-derived bone marrow cells (BMCs) from receptor mice were suppressed. Rejection reaction was alleviated by MSCs which exerted suppressive effects through T lymphocyte subsets and DCs.